Synthesis and Structural Diversity of Main Group Metal Coordination Complexes Constructed from V‐Shape Bis(3‐methyl‐1H‐pyrazole‐4‐carboxylic acid)alkane Ligands. Issue 17 (3rd May 2018) - Cheng, Meiling; Bao, Jinting; Wu, Yujuan; Yang, Bingxin; Wang, Qinghua; Sun, Lin; Liu, Qi
Abstract: Reaction of H2 L 1 /H2 L 2 /H2 L 3 with corresponding main group metal salts generated five complexes, [Mg(L 1 )(phen)(H2 O)3 ]⋅5H2 O (1, mononuclear), [Sr(CH3 OH)(L 1 )2 Sr(H2 O)2 ]2n ⋅nH2 O (2, 2D), [Ba(L 2 )(H2 O)3 ]n (3, 2D), [Pb(L 2 )(2, 2′‐bpy)]2n ⋅9nH2 O (4, 1D) and [Pb(L 3 )(phen)]2 ⋅2DMF (5, dinuclear) (H2 L 1 =1, 1'‐methylenebis(5‐methyl‐pyrazole‐4‐carboxylic acid, H2 L 2 = 2'‐methylenebis(3‐methyl‐pyrazole‐4‐carboxylic acid, H2 L 3 =1, 1'‐methylenebis(3‐methyl‐pyrazole‐4‐carboxylic acid; 2, 2'‐bpy=2, 2′‐bpyridine and phen=1, 10‐phenanthroline). In the zwitterionic complex1, a loop‐loop water‐water hydrogen bonded chain presented in the 3D supramolecular network, which was constructed by π⋅⋅⋅π interactions and hydrogen bonds. In CPs2 and3, the 1D inorganic M–O–M connectivity was built from Sr2 O16 and BaO9 polyhedra, respectively. The similar 24‐membered Pb2 (L 2 )2 /Pb2 (L 3 )2 macrocycle occurred in both 1D polymer4 and dinuclear complex5, with two 2, 2'‐bpy molecules located inside or two phen molecules outside each macrocycle respectively. The thermal and photoluminescent properties of1–5 in the solid state have also been investigated. Abstract : Five main group metal CPs/complexes containing bis(3‐methyl‐1H‐pyrazole‐4‐carboxylic acid)alkane ligands, varying from mono‐/di‐nuclear to 1D chain and 2D layer, were successfully synthesized and characterized. They display blue fluorescence in the solid state at room temperature.